PRINCIPLES OF CREATING EDUCATIONAL SYLLABLE (Ustozlar uchun, 2025)
This article explores the fundamental principles involved in creating an effective educational syllabus. It examines the role of learner-centered design, clear learning objectives, content selection and organization, alignment of teaching methods and assessment, flexibility, and inclusivity in syllabus development. The study emphasizes that a well-structured syllabus serves as a guiding framework for both teachers and learners, ensuring coherence between educational goals and learning outcomes. By applying these principles, educators can design syllabi that enhance learner engagement, support diverse learning needs, and improve the overall quality of the educational process.